Enhancing Learning Outcomes for Slow Learner Students through Differentiated Instruction in Social Studies Education - Hudriana, Rani; Sukinah, Sukinah (Papanda Publisher, 2025)
Slow learner students face significant challenges in Social Studies education due to difficulties with abstract concepts, chronological thinking, and information processing. This study examined the effectiveness of differentiated learning strategies in improving learning outcomes among slow learner students in junior high school Social Studies education. A classroom action research design was employed using the Kemmis and McTaggart model across two cycles. Three seventh-grade slow learner students were purposively selected from a public junior high school in East Kalimantan, Indonesia. Data collection utilized structured observations, pre-test and post-test assessments, and documentation. Differentiated learning strategies included visual materials, peer support systems, individualized guidance, and adaptive task modifications. Data analysis employed descriptive quantitative techniques to examine individual student progress. Substantial improvements were observed in both student engagement and academic achievement. Participation scores increased progressively across cycles, with students demonstrating enhanced attention, responsiveness, and motivation. Academic performance showed significant gains, with all participants achieving minimum mastery criteria by Cycle II. Student A improved from 55 to 75 points (+20), Student B from 50 to 79 points (+29), and Student C from 53 to 76 points (+23), representing substantial learning progress over the intervention period. The findings validate the effectiveness of differentiated instruction for slow learner students in Social Studies education. Results align with Tomlinson's theoretical framework and support previous research demonstrating positive impacts of adaptive teaching strategies. The study contributes empirical evidence for inclusive educational practices while highlighting the importance of individualized approaches in addressing diverse learning needs within regular classroom environments.